Cascade synthesis of dihydrobenzofuran via claisen rearrangement of allyl aryl ethers using FeCl 3 /MCM-41 catalyst - Sakate, Sachin S.; Shinde, Suhas H.; Kasar, Gayatri B.; Chikate, Rajeev C.; Rode, Chandrashekhar V. (Journal of Saudi Chemical Society, 2018)
Dihydrobenzofuran as one of the active ingredients of the naturally occurring motif is synthesized by using in situ generation of ortho allyl phenols. Aryl allyl ethers on reacting with catalytic amounts of non noble metal iron (III) chloride supported on MCM-41 under moderate reaction conditions yield dihydrobenzofuran. First step via Claisen rearrangement gives ortho allyl phenol followed by its in situ cyclization to yield dihydrobenzofuran in very good yields. Both Lewis as well as Brønsted acidity of the catalyst as evidenced by Py-FTIR studies was found to catalyze the cascade synthesis of dihydrobenzofuran. The scope of the present strategy was successfully demonstrated for several substrates with varying electronic effects for the synthesis of corresponding dihydrobenzofuran with high yields in a range of 71-86%.
Keywords: Aryl allyl ether; Claisen rearrangement; Dihydrobenzofuran; Ferric chloride; MCM-41

Steering the ester and gamma-valerolactone selectivities in levulinic acid hydrogenation - Kasar, Gayatri B.; Date, Nandan S.; Bhosale, P. N.; Rode, Chandrashekhar V. (Energy Fuels, 2018)
Both alkyl esters and γ-valerolactone (GVL) derived from levulinic acid (LA) have applications as renewable transportation fuel/fuel additives. Non-noble metal cobalt supported on La2O3 catalyst was developed for efficient cascade LA hydrogenation to GVL via esterification. LA hydrogenation in methanol alone yielded methyl levulinate (MeLA) as a major product along with 43% of GVL. Interestingly, hydrogenation in water gave almost complete selectivity to GVL; nevertheless, it was associated with significant metal leaching. Suppression of metal leaching and enhancement in selectivity to GVL could be achieved by a methanol/water (95:5) solvent system. XRD analysis of La2O3-supported catalysts evidenced the characteristic peaks of a mixture of La2O3 and La(OH)3 phases. Basicity, as well as acidity, of the catalyst as determined by CO2 and NH3 TPD was due to these La2O3, Co–La, and La(OH)3 phases which played an important role in directing the product selectivity in levulinic acid hydrogenation. At the low temperature of 160 °C, almost equal selectivities of MeLA (47%) and GVL (43%) were observed, while higher temperature (200 °C) favored further hydrogenation of MeLA to GVL (75%). Similarly, with an increase in reaction time to 9 h, the GVL selectivity achieved was as high as 80%. The selectivity to MeLA and GVL in LA hydrogenation over Co/La2O3 catalyst can be altered by suitably adjusting the reaction conditions.

Kinetics of hydrogenation of aqueous levulinic acid over bimetallic Ru-Ni/MMT catalyst - Kasar, Gayatri B.; Medhekar, Rucha S.; Bhosale, P. N.; Rode, V, Chandrashekhar (Industrial & Engineering Chemistry Research, 2019)
gamma-Valerolactone is one of the value-added products obtained from levulinic acid hydrogenation, having tremendous applications in fuels and chemicals. In this work, several monometallic and bimetallic compositions of Ru and Ni were prepared and evaluated for levulinic acid hydrogenation in an aqueous medium. The optimum composition of 0.5 wt % Ru and 5 wt % Ni on MMT was found to achieve 91% levulinic acid conversion with complete selectivity to gamma-valerolactone within 5 h at 220 degrees C and 250 psig H-2 pressure. XPS and H-2-TPR studies clearly showed that the electronic interactions between Ru-Ni leading to the synergism enhanced the catalytic efficiency of the Ru-Ni bimetallic catalyst. The average metal particle size by HRTEM was found to be in the range of 1.5-4.5 nm, having mixed cubic, oval, and spherical morphology, dispersed on the surface as well as within the layers of MMT. NH3-TPD showed a higher acidity due to both Lewis and Bronsted sites of the 0.5 wt % Ru-5 wt % Ni/MMT catalyst than individual MMT and monometallic catalysts. The presence of higher Lewis acidic sites preferred selective formation of GVL. Reaction kinetics was studied to propose the rate equation for this reaction based on which a plausible reaction pathway is proposed involving a first step dehydration of levulinic acid to an alpha-angelica lactone intermediate which then undergoes hydrogenation by dissociatively adsorbed H-2 to form gamma-valerolactone. The stability of our catalyst was proved by its recycle studies as well as by a hot filtration test.